A study of planar toroidal–poloidal beveling of monoblocks on the ITER divertor outer vertical target. (21st October 2019) - Gunn, J.P.; Hirai, T.; Corre, Y.; Escourbiac, F.; Grosjean, A.; Pitts, R.A.
Abstract: The design of the monoblocks constituting the ITER divertor vertical targets comprises a simple toroidal (i.e. toroidally-facing) bevel of 0.5 mm in order to magnetically shadow poloidal (i.e. poloidally-running) leading edges, arising from radial misalignments between toroidally neighbouring blocks, from parallel heat loads between and during edge-localised modes (ELMs). Previous studies suggest that excessive heating of long toroidal edges could also occur, possibly leading to melting during ELMs. Furthermore, despite the toroidal bevel, tiny regions of the poloidal leading edges known as 'optical hot spots', accessible along magnetic field lines through toroidal gaps, remain exposed to parallel heat flux from ELMs. The intense heat flux onto those optical hot spots could be large enough to trigger tungsten boiling. A possible solution at the outer vertical target is to implement a planar toroidal–poloidal bevel that would hide all poloidal and toroidal edges and eliminate the optical hot spot. It will be demonstrated that a reasonable 'shallow' toroidal–poloidal bevel solution solves all these problems with minimal trade-offs, under the condition that monoblocks on neighbouring plasma-facing units be well aligned poloidally in order to prevent the appearance of exposed leading edges, meaning, in the worst case, a stepwise downward shift of each toroidally upstream plasma-facing unit by  −2  ±  2 mm with respect to their downstream neighbours. A more deeply beveled solution has also been studied that is immune to poloidal misalignments, but which comprises important trade-offs in terms of higher heat load to the main wetted surface, and excessive ELM heat loads onto the magnetically shadowed side of the toroidal gaps. Unfortunately, due the inclination of magnetic flux surfaces, the planar toroidal–poloidal beveling solution does not work at the inner vertical target, meaning that its application at the outer target alone leaves the inner toroidal gaps unprotected. This, together with the technologically challenging requirement for a high degree of poloidal alignment of toroidally neighbouring plasma-facing units, has led to a decision not to apply the poloidal–toroidal bevel solution on the ITER vertical targets.